2021
DOI: 10.3390/ph14020138
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical Properties of Protoporphyrin IX, Pyropheophorbide-a, and Photofrin® in Different Conditions

Abstract: Photodynamic therapy (PDT) is an innovative treatment of malignant or diseased tissues. The effectiveness of PDT depends on light dosimetry, oxygen availability, and properties of the photosensitizer (PS). Depending on the medium, photophysical properties of the PS can change leading to increase or decrease in fluorescence emission and formation of reactive oxygen species (ROS) especially singlet oxygen (1O2). In this study, the influence of solvent polarity, viscosity, concentration, temperature, and pH mediu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 52 publications
1
43
0
Order By: Relevance
“…Use of beta-carotene proved beneficial in some patients (23,24); however, overall evidence is inadequate and results of a randomized controlled trial showed no improvement in light tolerance compared to placebo (25). Subjects with EPP require photoprotection in the UV-A and visible light regions, where the absorbance spectrum of protoporphyrin lies (26). The efficacy of commercially available sunscreens is commonly assessed in the UV-B and UV-A bandwidth; however, their protective effect against visible light is generally not significant and poorly characterized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of beta-carotene proved beneficial in some patients (23,24); however, overall evidence is inadequate and results of a randomized controlled trial showed no improvement in light tolerance compared to placebo (25). Subjects with EPP require photoprotection in the UV-A and visible light regions, where the absorbance spectrum of protoporphyrin lies (26). The efficacy of commercially available sunscreens is commonly assessed in the UV-B and UV-A bandwidth; however, their protective effect against visible light is generally not significant and poorly characterized.…”
Section: Introductionmentioning
confidence: 99%
“…The present study aimed at assessing the in vitro protective efficacy of six sunscreens by calculating PPF, as previously described in the 300-450 nm region and extended to the 300-700 nm wavelengths to include different absorption peaks of protoporphyrin IX: an intense Soret band centered around 406 nm and four weaker Q bands in the visible range (26).…”
Section: Introductionmentioning
confidence: 99%
“…The major emission peak was at 626 or 629 nm, which was followed by a smaller peak at 685 or 690 nm in case of 50% and pure methanol extractions, respectively. This resembles spectra of protoporphyrin IX acquired in water and pure methanol solutions [ 4 ]. Moreover, protoporphyrin IX is poorly soluble in water and was shown to aggregate at neutral pH [ 26 ].…”
Section: Resultsmentioning
confidence: 86%
“…Defects in different steps of heme synthesis in humans may lead to disorders, which are called porphyrias and are accompanied with accumulation of fluorescent porphyrin compounds (for a review see [ 3 ]). Among intermediate compounds in this pathway only protoporphyrin IX manifests bright fluorescence peaking at ~630 nm, which is excited by ~400 nm light [ 4 ]. The incorporation of Fe ion into protoporphyrin IX during heme formation leads to the loss of this fluorescence.…”
Section: Introductionmentioning
confidence: 99%
“…(a) Specification of the wavelength of interest As our TPS was designed for interstitial 5-ALA PDT using 635 nm homemade light sources (ONCOTHAI, Lille, France), the simulations were performed using the optical properties at 635 nm. This wavelength, corresponding to the Q I absorption band (i.e., to the fifth most intense absorption band) of PpIX [29], promotes light penetration in biological tissues while ensuring efficient excitation of molecular oxygen to its singlet state.…”
Section: Specifications Of the "Mcxyz" Program For Interstitial 5-ala Pdtmentioning
confidence: 99%